Safe Method of Collecting Leukaemia Cells from Patients with Acute Leukaemia for Use as Immunotherapy. Issue 5941 (16th November 1974) - Powles, R. L.; Lister, T. A.; Oliver, R. T. D.; Russell, J.; Smith, C.; Kay, H. E. M.; McElwain, T. J.; Fairley, G. Hamilton
Abstract : Leukaemia cells were collected from the blood of 72 untreated patients using a continuous-flow blood cell separator. The yield of cells was proportional to the number circulating in the patient, and up to 1 × 10 12 could be obtained in three hours. Complications of the procedure were mild, consisting of chills and shivering in 18% of patients. Leucopheresis at the time of diagnosis is an essential part of setting up a specific immunotherapy programme for patients with acute myelogenous leukaemia, and the lack of harmful side effects makes the collection of these cells ethically justified. The need for a centralized service to provide cells for this form of therapy is emphasized.